2023
DOI: 10.1002/adfm.202213374
|View full text |Cite
|
Sign up to set email alerts
|

Highly Transparent and Mechanically Robust Energy‐harvestable Piezocomposite with Embedded 1D P(VDF‐TrFE) Nanofibers and Single‐walled Carbon Nanotubes

Abstract: Herein, highly transparent, flexible, and ultrathin piezocomposite, in which electrospun poly(vinylidene fluoride-co-trifluoroethylene) [P(VDF-TrFE)] nanofibers (NFs) and aerosol-synthesized single-walled carbon nanotubes (SWCNTs) are embedded in elastomer matrix, is fabricated. The P(VDF-TrFE) NF mat is exploited as a piezoelectric layer of the piezocomposite while the SWCNT film is applied as a transparent conductive electrode thereof. The use of these 1D nanomaterials allows the piezocomposite not only to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 120 publications
0
10
0
Order By: Relevance
“…While laminating the CNT electrode decreased the transmittance of the device at 600 and 850 nm, the transmittance in the near‐infrared region increased significantly. This is attributed to the optical effects of the P3HT and CNT nanohybrid films 81,82 . This implies that stacking another solar cell that absorbs near‐infrared (NIR) light can boost the overall PCE by exploiting the high NIR transmittance of CNT‐based PSCs, which we tested and discussed later in this manuscript.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…While laminating the CNT electrode decreased the transmittance of the device at 600 and 850 nm, the transmittance in the near‐infrared region increased significantly. This is attributed to the optical effects of the P3HT and CNT nanohybrid films 81,82 . This implies that stacking another solar cell that absorbs near‐infrared (NIR) light can boost the overall PCE by exploiting the high NIR transmittance of CNT‐based PSCs, which we tested and discussed later in this manuscript.…”
Section: Resultsmentioning
confidence: 92%
“…This is attributed to the optical effects of the P3HT and CNT nanohybrid films. 81,82 This implies that stacking another solar cell that absorbs near-infrared (NIR) light can boost the overall PCE by exploiting the high NIR transmittance of CNT-based PSCs, which we tested and discussed later in this manuscript. The role of P3HT in CNT-based, metal-free, all-inorganic PSCs is crucial for achieving remarkable stability.…”
Section: Resultsmentioning
confidence: 99%
“…However, the variation of the enthalpy of fusion (Δ H f 0 ) with TrFE in P­(VDF-TrFE) is not established, with several studies utilizing reported values with variations of 5–10% from the experimentally used proportions. Δ H f 0 values of 93 and 67 J g –1 have been reported for PVDF and PTrFE homopolymers, respectively, with more recent studies reporting values around 40 J g –1 for P­(VDF-TrFE) with 20% TrFE. These values show Δ H f 0 in P­(VDF-TrFE) copolymer systems has a nonlinear response, and an extrapolation is not sufficient to properly estimate χ c for a large array of molar fractions.…”
Section: Resultsmentioning
confidence: 99%
“…2b) at 840, 1076, and 1281 cm -1 corresponds to the formation of β-phase. The relative fraction of the β-phase (840 cm -1 ) compared to that of α-phase (759 cm -1 ) was calculated as 82.9% [15]. Moreover, the SEM image (Fig.…”
Section: A Materials Characterizationmentioning
confidence: 99%
“…Electric charge conservation in the circuit can explain the frequency-dependent behavior of PENGs. As frequency rises, the tapping period of the PENG-connected circuit shortens, enabling more electrons to flow through each time and raising current and thereby the voltage generated [15]. This frequency-dependent increase in the piezoelectric output could be utilized for measuring mechanical vibrations, accelerations, and orientations [16].…”
Section: B Peng-based Sensor Characterizationmentioning
confidence: 99%